MicroRNAs in Helminth Parasites: A Systematic Review - Alizadeh, Zahra; Mahami-Oskouei, Mahmoud; Spotin, Adel; Ahmadpour, Ehsan; Cai, Pengfei; Sandoghchian Shotorbani, Siamak; Pashazadeh, Fariba; Ansari, Fereshteh; Mohammadi, Hamed (Current Molecular Medicine, 2022)
Background: MicroRNAs (miRNAs) are about 22-nucleotide, small, noncoding RNAs that control gene expression post-transcriptionally. Helminth parasites usually express a unique repertoire of genes, including miRNAs, across different developmental stages with subtle regulatory mechanisms. Objective: There is a necessity to investigate the involvement of miRNAs in the development of parasites, host-parasite interaction, immune evasion and their abilities to govern infection in hosts. MiRNAs present in helminth parasites have been summarized in the current systematic review (SR). Methods: Electronic databases, including PubMed, Scopus, ProQuest, Embase, and Google Scholar search engine, were searched to identify helminth miRNA studies published from February 1993 till December 2019. Only the published articles in English were included in the study. Results: A total of 1769 articles were preliminarily recorded. Following the strict inclusion and exclusion criteria, 105 studies were included in this SR. Most of these studies focused on the identification of miRNAs in helminth parasites and/or probing of differentially expressed host miRNA profiles in specific relevant tissues, while 12 studies aimed to detect parasite-derived miRNAs in host circulating system and 15 studies characterized extracellular vesicles (EV)-derived miRNAs secreted by parasites. Conclusion: In the current SR, information regarding all miRNAs expressed in helminth parasites has been comprehensively provided and the utility of helminth parasitesderived miRNAs in diagnosis and control of parasitic infections has been discussed. Furthermore, functional studies on helminth-derived miRNAs have also been presented.
Keywords: parasites